Development of a novel drug delivery system: chitosan nanoparticles entrapped in alginate microparticles. (June 2014) - Garrait, Ghislain; Beyssac, Eric; Subirade, Muriel
Abstract A novel carrier using chitosan nanoparticles entrapped into alginate microparticles is proposed for protecting molecules of interest from degradation in the digestive tract. The effects of polymer concentration, sonication, stirring, pH, and processing conditions on the physical characteristics of the carrier were studied. FITC and RBITC were used to localise the polymers within particles using CLSM. Diffusion of amaranth red (AR) from nanoparticles was quantified during dissolution under gastric and intestinal conditions. Under optimal preparation conditions, the size distribution of nanoparticles loaded with AR was uniform (690 nm) with an encapsulation efficacy of 21.9%. Alginate microparticles (285 µm) containing a homogenous distribution of nanoparticles and polymers were obtained. At gastric pH, the carrier released less than 5% of the loaded AR and, at intestinal pH, the release was rapid and complete. The drug carriers developed shows a promising use as a vehicle suitable to protect molecules of interest after oral administration.